In vitro establishment and multiplication of Aloe vera L. shoots - Naivy Pérez Alonso; Alina Capote; Anabel Pérez; Leticia Gómez; Elio Jiménez (Biotecnología Vegetal, 2015)
The high demand of Aloe vera L. in the pharmaceutical and cosmetic industries has caused that the traditional crop is insufficient to satisfy the current market. In Cuba, this plant is used as a constituent of many pharmaceutical and cosmetic products. At present, a large part of Aloe raw material is imported due to the lack of sufficiently large populations to meet all the demand. In vitro propagation is one of the alternatives to increase the availability of biomass of this specie. For this reason, this research was carried out in order to study the effect of the time of collecting plant material and conditions disinfection to establishment in vitro shoots. Besides, the use of growth regulators in multiplication phase was studied. The results showed that in vitro establishment of apices with 93% microbial contamination-free explants was achieved taking plant material in the dry season and disinfecting with 2.0% sodium hypochlorite for 15 min. In the multiplication phase were obtained best results in culture medium containing the combination of 2.0 mg l-1 of 6-BAP and 0.5 mg l-1 of AIB, making a transversal cut to shoot. In these conditions, the multiplication coefficients obtained was stable during nine subcultures with maximum valour of 5.1.